### Simple and best practice solution for 12x^2+6x-9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

### Solution for 12x^2+6x-9=0 equation:

Simplifying 12x

^{2}+ 6x + -9 = 0 Reorder the terms: -9 + 6x + 12x

^{2}= 0 Solving -9 + 6x + 12x

^{2}= 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-3 + 2x + 4x

^{2}) = 0 Ignore the factor 3.

#### Subproblem 1

Set the factor '(-3 + 2x + 4x^{2})' equal to zero and attempt to solve: Simplifying -3 + 2x + 4x

^{2}= 0 Solving -3 + 2x + 4x

^{2}= 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. + x + x

^{2}= 0 Move the constant term to the right: Add '' to each side of the equation. + x + + x

^{2}= 0 + Reorder the terms: + + x + x

^{2}= 0 + Combine like terms: + = + x + x

^{2}= 0 + x + x

^{2}= 0 + Combine like terms: 0 + = x + x

^{2}= The x term is x. Take half its coefficient (). Square it () and add it to both sides. Add '' to each side of the equation. x + + x

^{2}= + Reorder the terms: + x + x

^{2}= + Combine like terms: + = + x + x

^{2}= Factor a perfect square on the left side: (x + )(x + ) = Calculate the square root of the right side: Break this problem into two subproblems by setting (x + ) equal to and

#### Subproblem 1

x + = Simplifying x + = Reorder the terms: + x = Solving + x = Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '' to each side of the equation. + + x = + Combine like terms: + = + x = + x = + Combine like terms: + = x = Simplifying x =#### Subproblem 2

x + = Simplifying x + = Reorder the terms: + x = Solving + x = Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '' to each side of the equation. + + x = + Combine like terms: + = + x = + x = + Combine like terms: + = x = Simplifying x =#### Solution

The solution to the problem is based on the solutions from the subproblems. x = {, }#### Solution

x = {, }#### You can always share this solution

### See similar equations:

| 5p=8p+18 || 2(x+3)=4x || 4h+2h=8 || 6n-4n=0 || 3h+17h= || 6XX=0 || X^2+-4x=0 || p-4p=21 || 3(2n-5)+45=60 || 6x-7(3x+4)=5x-8 || 4(n+7)+6=98 || x+3x+15=-5x || 4xx=0 || z^4+2iz^2+3=0 || x+3x+21=38 || 3xx+24=0 || =x++x || 3y(2y-1)=0 || 8=t^2+60t+1 || x^2y+y^2=0 || 3x+x=20 || =kk || 14=2(x+6) || =p+p || =6y || 18=6b-3b || 5(2x-1)=7x+10 || 3p-9=36 || f+5=48 |

### Equations solver categories

### Most Used Actions

\mathrm{simplify} | \mathrm{solve\:for} | \mathrm{expand} | \mathrm{factor} | \mathrm{rationalize} |

Our online expert tutors can answer this problem

Get step-by-step solutions from expert tutors as fast as minutes. Your first 5 questions are on us!

In partnership with

You are being redirected to Course Hero

Correct Answer :)

Let's Try Again :(

Try to further simplify

### Related

### Number Line

### Graph

### Examples

factor-calculator

factor x^{2}-6x+9

en

Table of Contents

### What is the factor of x2 6x 9?

Look: (x + 3)2 = x2 + 6x + 9, and (x – 3)2 = x2 – 6x + 9! Here 9 can be written as (−3)2, so the middle term is 2(−3)x = −6x. So when the sign of the middle term is negative, the trinomial may be factored as (a – b)2&#;.

Factors of −36 | Sum of the factors |
---|---|

… | … |

### What are the zeros of the polynomial x2 6x 9?

so the zero of the polynomial is 3.

### How many solutions does x2 6x 9 0?

Solving xx+9 = 0 by Completing The Square . This quadratic equation has one solution only.

### What is the factor of x2 6x 16?

That is, x 2 &#; 6x &#; 16 = (x + 2)(x &#; 8). The last step is to set each of these factors equal to zero and solve as shown&#;.Solving Using Factoring.

Factors of 16 | Sum |
---|---|

2 and -8 | 2 + (-8) = -6 |

-2 and 8 | -2 + 8 = 6 |

4 and -4 | 4 + (-4) = 0 |

### What is the answer of x2 ?

Answer Expert Verified In the given problem: The solution for the quadractic equation of x²= is x= ±10, in quadractic equation it is possible to have two solutions. The standard form for that equation is x² &#; = 0, based from x² +0x = 0 (standard form).

### Is 4x 2 6x 9 a perfect square?

Yes, 4&#;2 + 6x + 9 is a perfect square. (2x + 3)2.

### How do you find the zeros of a quadratic polynomial?

Let&#;s understand the relationship between zeros and coefficients of a quadratic polynomial. If α and β are zeros of a quadratic polynomial, x2+bx+c=0 x 2 + b x + c = 0 , the sum of zeros is equal to the negative of b and the product of zeros is equal to the constant term c .

### What are the factors of the 9 0?

Detailed Answer: The Greatest Common Factor (GCF) for 9 and 0, notation CGF(9,0), is 9. Explanation: The factors of 9 are 1,3,9; The factors of 0 are .

### What are the factors of 2x 2 3x 54?

Step-by-step explanation: Therefore, the factors are x + 6 and 2x − 9.

### What&#;s the perfect square rule?

In the case of a perfect square, the middle term is the first term multiplied by the last term, and then multiplied by 2. In other words, the perfect square trinomial formula is: a 2 ± a b + b 2 a^{2} \pm ab + b^{2} a2±ab+b2.

### Is 16x 9 a perfect square?

In addition to factoring 16x^2+9, we will also verify that our answer is correct by calculating the product of the factors we found. Before we begin, note that 16 and 9 are both perfect squares.

### What is the formula of quadratic polynomial?

Quadratic Polynomial Formula A quadratic polynomial is of the form p(x): ax2+bx+c, where a≠0. The quadratic formula to find the solution to a quadratic equation is given by: x=−b±√b2−4ac2a x = − b ± b 2 − 4 a c 2 a , in which, a is the coefficient of x2 and is also called the quadratic coefficient.

### How do you factor 16&#;2 40x 25?

1 Answer

- Compare a2−2ab+b2 to 16&#;2−40x+
- Then, 2ab=2×4x×5=40x , as given in the expression.
- 16&#;2−40x+
- The factors are 4x−5,4x−5.

### What is the HCF of 0 and 9?

The factors of 9 are 1, 3 and 9. The factors of 0 are 0 and 1. So, the Greatest Common Factor for these numbers is 1 because it divides all them without a remainder. Read more about Common Factors below.

Anya babbled upset and, with a trembling voice, asked even more quietly, Maybe your wife is waiting for you at home. No, what are you. I am lonely, like a finger, like an aspen leaf, just can the three of us be able to. I knelt down in front of Anya sitting on a chair and gently hugged her and pressed against her body.

She ran her hands through my hair.

## 9 factor 2 6x

It was clear from her manners. that she was used to getting everything from life. what he wants. It was clear. that I was on her wishlist.

69. Una factorización de la expresión X^2 - 6x + 9, esAfter pouring a pinch of sugar and a few drops of jam into the bottle, I put it near the shed, the walls of. Which were full of flies, and I often smacked them there with a fly swatter when they really got me. Sneaking up and placing the bottle next to the wall, I stepped aside and began to watch. Within a few minutes, two flies were crawling inside.

### Now discussing:

- Td lost card debit
- Track top adidas firebird
- 12 concrete planter
- Lml duramax short block
- Ryzen 5 3600 g
- R kelly ringtone download
- Sam pak wife
- Daschund rescue ct
- Driver handbook florida
- Japanese font
- Business analyst resume linkedin

We sat for a long time by the sea and listened to the sound of the surf. Im there for the first time. Yes. First.

**404**405 406